Scaling readiness: Accelerating the scaling of RTB interventions. Newsletter No.2 - Sartas, Murat; Schut, Marc; Asten, Piet J.A. van; Thiele, Graham; Proietti, Claudio; Leeuwis, Cees (2017)
This is the second of the series of newsletters that will capture our efforts to develop an approach that will accelerate the scaling of innovations in the CGIAR Research Program on Roots, Tubers and Bananas (RTB). The newsletters will capture the major concepts of Scaling Readiness, activities, and information about the RTB cases in which we are developing and testing the approach. The Scaling Readiness project is an Earmarked Funded project under RTB Cluster 5.4 and is implemented by Wageningen University, IITA, Bioversity International, CIAT and CIP.